A 3D view of the Hydra I cluster core- II. Stellar populations. Issue Volume 10:Issue S309(2014) (9th February 2015) - Barbosa, Carlos Eduardo; Arnaboldi, Magda; Hilker, Michael; Coccato, Lodovico; Richtler, Tom; de Oliveira, Cláudia Mendes
Abstract: Several observations of the central region of the Hydra I galaxy cluster point to a multi-epoch assembly history. Using our novel FORS2/VLT spectroscopic data set, we were able to map the luminosity-weighted age, [Fe/H] and [α/Fe] distributions for the stellar populations around the cD galaxy NGC 3311. Our results indicate that the stellar populations follow the trends of the photometric substructures, with distinct properties that may aid to constrain the evolutionary scenarios for the formation of the cluster core.